ChemInform Abstract: Pyroxene‐Type Compounds NaM3+Ge2O6, with M: Ga, Mn, Sc and In. Issue 44 (4th November 2014) - Redhammer, Guenther J.; Tippelt, Gerold
Abstract The structures of the title compounds are determined by single crystal XRD.